Fuzzy Best Dominants for Certain Fuzzy Differential Subordinations - Cătaş, Adriana (Journal of Advances in Applied & Computational Mathematics, 2022)
This paper aims to present a survey on certain fuzzy subordination properties for analytic functions defined in the open unit disk. The new results are derived by considering a certain differential operator. By making use of two differential properties of the operator we determine sufficient conditions to find the fuzzy best dominants for several fuzzy differential subordinations. Some interesting further fuzzy consequences are also considered.